OPPORTUNITIES AND METHODOLOGICAL CHALLENGES OF USING ARTIFICIAL INTELLIGENCE TOOLS IN FOREIGN LANGUAGE TEACHING - Shodmonova Dildora Davron qizi (International Journal of Literature and Language Studies, 2026)
The rapid progress of artificial intelligence (AI) technologies, particularly generative language models such as ChatGPT, DeepL, Claude, and specialized AI language learning platforms, is initiating a fundamental transformation in foreign language education. This paper examines the opportunities and methodological challenges of integrating AI tools into foreign language classrooms. The study focuses on personalized learning, automated corrective feedback, material preparation for teachers, and the development of learner autonomy. Alongside these advantages, methodological risks such as AI hallucinations, grammatical and pragmatic inaccuracies, academic integrity issues, and potential loss of deep cognitive processing are critically evaluated. Based on current educational research, a practical four-phase pedagogical model is proposed for the reflective integration of AI into foreign language instruction.